Hunger in the primary school setting: evidence, impacts and solutions according to school staff in the North East of England, UK. Issue 2 (17th February 2020) - Gooseman, Annabel; Defeyter, Margaret Anne; Graham, Pamela Louise
ABSTRACT: The issue of 'holiday hunger' (i.e. food insecurity during school holidays) has received increased attention in recent years, though research in this area is limited. Through qualitative, semi-structured interviews, the current study investigated the views of 12 primary school staff on the existence, impacts and potential solutions to holiday hunger. Thematic analysis revealed holiday hunger forms part of a broader, year-round experience of deprivation and poor nutritional habits. Staff proposed a need for a multi-agency approach to address a range of complex, inter-related needs. Additionally, the findings highlighted a need to address poverty stigma in the development of familial support.